2023
DOI: 10.1007/s00044-023-03068-0
|View full text |Cite
|
Sign up to set email alerts
|

Promising Schiff bases in antiviral drug design and discovery

Abstract: Emerging and re-emerging illnesses will probably present a new hazard of infectious diseases and have fostered the urge to research new antiviral agents. Most of the antiviral agents are analogs of nucleosides and only a few are non-nucleoside antiviral agents. There is quite a less percentage of marketed/clinically approved non-nucleoside antiviral medications. Schiff bases are organic compounds that possess a well-demonstrated profile against cancer, viruses, fungus, and bacteria, as well as in the managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 128 publications
0
4
0
Order By: Relevance
“…A few azo-azomethine metal complexes have been used extensively in technology due to their photophysical and energy-transfer capabilities. Because of their stability, electroactivity, thermochromism, and photochromism, Schiff base compounds make excellent intermediates for a variety of uses. Numerous reviews revealed that the metallo-organic chemistry of such compounds significantly affected how they acted biologically, highlighting the role played by metals as catalysts in a variety of biological processes. Higher electronegative atoms’ connected bonding orbitals and electrons can be adsorbed on metal surfaces due to their electrons’ C=N faction planarity. This substance contributes significantly to the development of inorganic biochemistry and is used as a substrate in ring closure, cycloaddition, and replacement reactions to produce a variety of biologically active compounds. …”
Section: Introductionmentioning
confidence: 99%
“…A few azo-azomethine metal complexes have been used extensively in technology due to their photophysical and energy-transfer capabilities. Because of their stability, electroactivity, thermochromism, and photochromism, Schiff base compounds make excellent intermediates for a variety of uses. Numerous reviews revealed that the metallo-organic chemistry of such compounds significantly affected how they acted biologically, highlighting the role played by metals as catalysts in a variety of biological processes. Higher electronegative atoms’ connected bonding orbitals and electrons can be adsorbed on metal surfaces due to their electrons’ C=N faction planarity. This substance contributes significantly to the development of inorganic biochemistry and is used as a substrate in ring closure, cycloaddition, and replacement reactions to produce a variety of biologically active compounds. …”
Section: Introductionmentioning
confidence: 99%
“…Many SBs are known to be used in a broad range of fields, including electroluminescence, 14–17 luminescence, 18–20 energy materials, 21 analytical chemistry, 22 food industry, 23 catalysis, 24–26 dye industries, 27,28 manufacturing of polymer‐based substances, 29,30 use as detectors, 31–33 organic optoelectronic substances, 34,35 and pharmacological agents 36 . Pharmacological applications include anti‐inflammatory, 37,38 anti‐tumor, 39,40 anti‐convulsant, 41–44 anti‐fungal, 44–46 painkillers, 47 anti‐bacterial, 48–50 anti‐malarial, 51,52 anti‐viral, 53–57 anti‐helminthic, 58,59 anti‐oxidants, 60–62 and DNA interaction 63 and further along (Scheme 2). Because of their DNA‐binding characteristics, SB metal complexes have garnered significant interest over the past 10 years 64,65 …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some reports correlated the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection with increasing probability of cancer development in different organs [38][39][40] and due to the unique mechanisms of action and the versatility of metallodrugs in interacting with biological molecules, e.g., targeting specific crucial steps for cancer cells and also interfering with the viral replication process, either by directly targeting viral components or by modulating host cellular mechanisms, metallodrugs might represent a promising frontier in both cancer and antiviral therapies [41,42]. In this sense, cobalt Schiff base complexes have gained attention, mainly due to their ability to induce apoptosis in cancer cells [43,44] and inhibit viral replication by targeting different viral enzymes [45,46], which offers a promising avenue for the development new therapies.…”
Section: Introductionmentioning
confidence: 99%